Persepsi Pengguna Platform Quora Mengenai Urgensi Perjanjian Perkawinan dalam Membentuk Keluarga Sakinah - Maulidya, Aisyah Firyal (Maliki Interdisciplinary Journal, 2025)
The marriage agreement occupies a very important position in marriage. It not only contains an agreement regarding property, but also other important things such as consequences when the husband / wife neglects their obligations. Eastern cultural culture is still very visible in Indonesian society which causes a taboo view of marriage agreements. In addition, the flow of globalization and technological advances is very possible for the dissemination of legal education and seeing the current views of society on various legal issues including marriage agreements. This study aims to analyze the perception of the Indonesian people about the urgency of marriage agreements in forming a sakinah family. Through the Quora platform as a medium for exchanging information with observation methods on the platform on related topics and also library research on relevant literature.